Policy Implications of School Autonomy on Educational Quality in Indonesian Public Schools - Chusnul Chotimah; Aprillia priseyla Longdong; Septi Dwi Nursanti (International Journal of Educational Evaluation and Policy Analysis, 2024)
This article analyzes school autonomy policies in Indonesia and their implications for educational quality. Studying schools with varying degrees of autonomy, the study examines the relationship between decentralized management practices and student performance. The findings suggest that while autonomy can lead to better educational outcomes, its success depends largely on the capacity of school leadership and access to resources. The paper concludes with policy recommendations for balancing autonomy with support systems to ensure quality education.